Obstacles to initiating an action research study at a former Department of Education and Training (DET) school : the case of Kayamandi High School - Mokotso, Bontle Adelaide (Stellenbosch : Stellenbosch University, 2012)
Thesis (M Ed) -- University of Stellenbosch, 1999.